Studi Komparatif Tentang Sariqah dalam Perspektif Empat Mazhab - Mimin Rohimin (Justicia Religia, 2025)
Sariqah (theft) is one of the ḥadd crimes in Islamic criminal law that carries specific requirements regarding its elements, conditions, and prescribed punishment. The four major Sunni schools of law Hanafi, Maliki, Shafi‘i, and Ḥanbali agree that sariqah refers to the unlawful and covert taking of another person’s property. However, they differ significantly in determining the nisab (minimum value of stolen property), the criteria for protected property (hirz), the types of goods that qualify for hadd, and the exceptions that may prevent the implementation of the punishment of amputation. This study aims to comparatively analyze the perspectives of the four schools concerning the essential conditions and elements required to impose criminal liability for sariqah, as well as to examine the textual and jurisprudential foundations underlying these differences. Using a library research method and a comparative approach, the findings reveal that the Ḥanafi school adopts a stricter stance on the nisab and the nature of stolen goods, the Maliki school emphasizes social stability and the relative value of the property, the Shafi‘i school focuses closely on the textual stipulations of hadith, while the Ḥanbali school tends to follow the apparent meaning of the scriptural evidence. These variations demonstrate that Islamic criminal law allows for interpretive flexibility and a wide scope of ijtihad in responding to diverse social contexts. This research contributes to the broader discourse on Islamic criminal jurisprudence and enriches comparative legal studies concerning contemporary issues in jinayah.